Aspirin for primary prevention of cardiovaascular events: what are the evidances? - Yenny, Yenny (Faculty of Medicine, Trisakti University, 2019)
Cardiovascular disease (CVD) is the leading cause of mortality in the United States, accounting for about 1 in 3 deaths.(1) In view of the healthcare and economic burdens of cardiovascular disease, the public health aim should be the prevention of cardiovascular events through risk factor optimization.